The Association between Self-Compassion on Posttraumatic Growth among Female Victims of Verbal Abuse - Andi Fikriyah Fadhilah; Ahmad Ridfah; Novi Yanti Pratiwi (Universitas Ahmad Dahlan, 2026)
This cross-sectional study examined the association between self-compassion and posttraumatic growth (PTG) among 399 female victims of verbal abuse aged 18-24 years recruited via accidental sampling across Indonesia. Data were collected using validated Indonesian versions of the Self-Compassion Scale (SCS, 19 items, Cronbach's α = .93) and Posttraumatic Growth Inventory (PTGI, 15 items, Cronbach's α = .87), analyzed via binary logistic regression. Self-compassion showed a significant positive association with higher odds of PTG (OR = 1.032, 95% CI [1.003, 1.063], p = .030), although the effect was small (Nagelkerke R² = 0.017) and model discrimination poor (AUC = 0.497, Hosmer-Lemeshow p < .001). Findings highlight self-compassion's concurrent statistical relationship with PTG in collectivistic contexts, with implications for mindfulness-based interventions. Limitations include cross-sectional design and model under-specification.